Atlantic overturning inferred from air-sea heat fluxes indicates no decline since the 1960s - Jens Terhaar; Linus Vogt; Nicholas P. Foukal (Nature Communications)
Abstract The Atlantic Meridional Overturning Circulation (AMOC) is crucial for global ocean carbon and heat uptake, and controls the climate around the North Atlantic. Despite its importance, quantifying the AMOC’s past changes and assessing its vulnerability to climate change remains highly uncertain. Understanding past AMOC changes has relied on proxies, most notably sea surface temperature anomalies over the subpolar North Atlantic. Here, we use 24 Earth System Models from the Coupled Model Intercomparison Project Phase 6 (CMIP6) to demonstrate that these temperature anomalies cannot robustly reconstruct the AMOC. Instead, we find that air-sea heat flux anomalies north of any given latitude in the North Atlantic between 26.5°N and 50°N are tightly linked to the AMOC anomaly at that latitude on decadal and centennial timescales. On these timescales, air-sea heat flux anomalies are strongly linked to AMOC-driven northward heat flux anomalies through the conservation of energy. On annual timescales, however, air-sea heat flux anomalies are mostly altered by atmospheric variability and less by AMOC anomalies. Based on the here identified relationship and observation-based estimates of the past air-sea heat flux in the North Atlantic from reanalysis products, the decadal averaged AMOC at 26.5°N has not weakened from 1963 to 2017 although substantial variability exists at all latitudes.